The Effectiveness of The Jigsaw Cooperative Learning Model Assisted by Wordwall Application on Citizenship Competence (A Quasi-Experimental Study of 8th Grade Students at SMP Muhammadiyah Bumiayu) - Iftikhoor Dwi Ambarwati; Ratna Kartikawati; Elly Hasan Sadeli (UM Purwokerto Press, 2024)
This study aims to determine the extent to which the Jigsaw cooperative learning model, assisted by the Wordwall application, affects the formation of citizenship competence in the subject of the Youth Pledge within the framework of Bhinneka Tunggal Ika. The research method used quasi-experimental with a Nonequivalent Control Group Design. The sample includes Grade VIII A as the control group (n=35) and Grade VIII B as the experimental group (n=35). Data collection techniques included tests, questionnaires, observations, interviews, and documentation, analyzed using the Paired Sample Test and Independent Sample T-Test with a significance level of 5%, resulting in 0.000 0.05, indicating that the Jigsaw cooperative learning model assisted by the Wordwall application is effective in developing students' citizenship competence. The results show a significant difference between the experimental and control groups. Citizenship knowledge improved to 86% in the experimental group compared to 76% in the control group, citizenship skills to 86% compared to 76%, and citizenship attitudes or character to 79% compared to 64%. The Effect Size test result was 2.166, categorized as a high effect. This is evidenced by the study's findings that the Jigsaw cooperative learning model assisted by the Wordwall application significantly affects students' citizenship competence in the subject of the Youth Pledge within the framework of Bhinneka Tunggal Ika at SMP Muhammadiyah Bumiayu.